Deep brain stimulation for Parkinson’s disease: systematic review with meta-analysis and trial sequential analysis - Christian Gluud; Janus C Jakobsen; Sophie Juul; Pascal Faltermeier; Johanne Juul Petersen; Caroline Barkholt Kamp; Annemette Løkkegaard (BMJ Medicine, 2024)
Objective To assess the benefits and harms of deep brain stimulation for Parkinson’s disease.Design Systematic review with meta-analysis and trial sequential analysis.Data sources Cochrane Central Register of Controlled Trials (CENTRAL), Medline, Embase, Latin American and Caribbean Health Sciences Literature (LILACS), and other sources, from inception to 9 May 2023.Eligibility criteria for selecting studies Randomised clinical trials of deep brain stimulation with antiparkinsonian drug treatment use versus antiparkinsonian drugs only (primary comparison, seven trials) for Parkinson’s disease. Other comparisons were deep brain stimulation versus surgery with sham stimulation (three trials) and versus resective surgery (two trials).Results Primary outcomes were all cause mortality, serious adverse events, and disease specific symptoms. In seven trials, 1125 participants were randomised to receive deep brain stimulation with antiparkinsonian drugs versus antiparkinsonian drugs only. All results had a high risk of bias and the certainty of the evidence was very low for all primary outcomes. Information size was insufficient for assessing all cause mortality (risk ratio 2.69, 95% confidence interval (CI) 0.79 to 9.24; I2=0.0%; τ2=0.00; P=0.12; four trials). Meta-analysis showed that deep brain stimulation increased the risk of serious adverse events (risk ratio 2.36, 95% CI 1.37 to 4.09; I2=73.7%; τ2=0.24; P<0.01; six trials) mainly because of an increased risk of perioperative complications, such as cerebral haemorrhages and postoperative confusion, and hardware related events, such as infection at the stimulator site, dislocation of the device, or reoperations. Meta-analyses indicated that deep brain stimulation might reduce some symptoms specific to Parkinson's disease, but assessment of disease specific symptoms in these trials had methodological limitations, including not reporting overall symptom scores.Conclusions The certainty of evidence was very low for all primary outcomes, and based on the included evidence, the beneficial effects were questionable because of methodological limitations. Compared with only antiparkinsonian drug treatment, deep brain stimulation with antiparkinsonian drugs seemed to increase the risk of serious adverse events, mainly because of perioperative complications and hardware related events. Conducting randomised clinical trials of adequate methodological quality to effectively evaluate the effects of deep brain stimulation is crucial.Systematic review registration PROSPERO CRD42022306556.